2023
DOI: 10.3389/fpls.2023.1182745
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral cross-incompatibility between Camellia oleifera and C. yuhsienensis provides new insights for hybridization in Camellia spp

Abstract: Camellia yuhsienensis was used to cross with Camellia oleifera to improve the resistance of oil camellia anthracnose. However, unilateral cross-incompatibility (UCI) between C. oleifera and C. yuhsienensis was found during the breeding process. Five C.oleifera cultivars and four C. uhsienensis materials were tested to confirm the UCI between C. oleifera and C. yuhsienensis. ‘Huashuo’ (HS) and ‘Youza 2’ (YZ2) were used to represent these two species to characterize the UCI, including pollen tube growth, fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Most vegetable oils are rich in unsaturated fatty acids [20]. Camellia oleifera Abel., belonging to genus Camellia of the family Theaceae, is a woody oil crop widely cultivated in Southern China [21,22]. Extracted Camellia oleifera seed oil is abundant in unsaturated fatty acids, mainly oleic acid and linoleic acid, accounting for 90% of the total [22].…”
Section: Introductionmentioning
confidence: 99%
“…Most vegetable oils are rich in unsaturated fatty acids [20]. Camellia oleifera Abel., belonging to genus Camellia of the family Theaceae, is a woody oil crop widely cultivated in Southern China [21,22]. Extracted Camellia oleifera seed oil is abundant in unsaturated fatty acids, mainly oleic acid and linoleic acid, accounting for 90% of the total [22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, A. cerana can act as the native pollinator for some species of Camellia , such as Camellia reticulata and Camellia saluenensis . On the contrary, recent research has revealed that Camellia meiocarpa and C. yuhsienensis are unilaterally cross-incompatible, a unidirectional inter/intrapopulation reproductive barrier when both parents are self-compatible, thus providing new opportunities for the creation of innovative germplasm of C. oleifera through distant hybridization . Here, we propose optimistically that it will be possible to use distant hybridization to solve the pollination deficient problems in the C. oleifera oil production industry in the future.…”
mentioning
confidence: 99%